Digital Transformation in Villages: A Policy Implementation Approach in Kajowair Village, Nusa Tenggara Timur - Hieng, Beatrix Brightany; Prabawati, Ni Putu Anik (Universitas Pattimura, 2025)
This study investigates the implementation of digital transformation policies in Kajowair Village, Nusa Tenggara Timur, through the Village Information and Service Management System (Simpeldesa). Utilizing a qualitative descriptive approach, data were collected via in-depth interviews, field observations, document analysis, and literature reviews involving 15 key informants, including village officials and community members. The findings reveal that Simpeldesa implementation reflects strong policy disposition and effective coordination facilitated by a simplified bureaucratic structure. However, limited communication outreach, inadequate infrastructure, and low digital literacy pose significant challenges to inclusive digitalization. Despite only 51.88% internet penetration, village-level commitment and resource allocation have enabled substantial initial progress, with 50% of administrative data successfully digitized. This research offers new insights into rural e-government implementation by applying Edward III’s policy implementation framework—emphasizing communication, resources, disposition, and structure. The novelty lies in its micro-level focus on a single village, rarely explored in policy studies. The study contributes to the theoretical discourse on digital governance in rural areas while providing practical recommendations for enhancing infrastructure, community engagement, and digital capacity-building. These findings serve as a valuable reference for policymakers and scholars seeking to understand and replicate successful digital transformation models in similar village contexts.